Natural Disease Course of Ulcerative Colitis During the First Five Years of Follow-up in a European Population-based Inception Cohort—An Epi-IBD Study. (5th October 2018) - Burisch, Johan; Katsanos, Konstantinos H; Christodoulou, Dimitrios K; Barros, Luisa; Magro, Fernando; Pedersen, Natalia; Kjeldsen, Jens; Vegh, Zsuzsanna; Lakatos, Peter L; Eriksson, Carl; Halfvarson, Jonas; Fumery, Mathurin; et al.
Abstract: Background and Aims: Few population-based cohort studies have assessed the disease course of ulcerative colitis [UC] in the era of biological therapy and widespread use of immunomodulators. The aim of this study was to assess the 5-year outcome and disease course of patients with UC in the Epi-IBD cohort. Methods: In a prospective, population-based inception cohort of unselected patients with UC, patients were followed up from the time of their diagnosis, which included the collection of their clinical data, demographics, disease activity, medical therapy, and rates of surgery, cancers, and deaths. Associations between outcomes and multiple covariates were analysed by Cox regression analysis. Results: A total of 717 patients were included in the study. During follow-up, 43 [6%] patients underwent a colectomy and 163 [23%] patients were hospitalised. Of patients with limited colitis [distal to the left flexure], 90 [21%] progressed to extensive colitis. In addition, 92 [27%] patients with extensive colitis experienced a regression in disease extent, which was associated with a reduced risk of hospitalisation (hazard ratio [HR]: 0.5 95% CI: 0.3–0.8]. Overall, patients were treated similarly in both geographical regions; 80 [11%] patients needed biological therapy and 210 [29%] patients received immunomodulators. Treatment with immunomodulators was found to reduce the risk of hospitalisation [HR: 0.5 95% CI: 0.3–0.8]. Conclusions: Although patients in this population-based cohort were treated more aggressively with immunomodulators and biological therapy than in cohorts from the previous two decades, their disease outcomes, including colectomy rates, were no different. However, treatment with immunomodulators was found to reduce the risk of hospitalisation.